2008
DOI: 10.1590/s1516-89132008000600017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidants in fresh cut radishes during the cold storage

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
2
5
0
5
Order By: Relevance
“…Pieces that were immersed in the solution only containing the antioxidants had the highest scores for all assessment days, due to decreased browning of these pieces. Similar results were reported by Lee, Lee and Park (2007) and Aguila et al (2008), who observed a positive effect of ascorbic and citric acid when used individually on the control of browning in minimally-processed sliced taro and radishes, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Pieces that were immersed in the solution only containing the antioxidants had the highest scores for all assessment days, due to decreased browning of these pieces. Similar results were reported by Lee, Lee and Park (2007) and Aguila et al (2008), who observed a positive effect of ascorbic and citric acid when used individually on the control of browning in minimally-processed sliced taro and radishes, respectively.…”
Section: Resultssupporting
confidence: 89%
“…The b* value was positive, indicating a tendency toward yellow. del Aguila et al (2008) reported similar chromatic parameters for shredded radish: L = 74.54, a = −0.55 and b = 3.90. Chromatic parameters for leaves were typical for green leafy vegetables: L = 46.47 ± 3.93, a = −11.45 ± 0.27 and b = 28.64 ± 3.25.…”
Section: Colormentioning
confidence: 78%
“…Aguila et al (2008) observaram que rabanetes minimamente processados e tratados com ácido cítrico apresentaram aumento no teor de sólidos solúveis, mas não houve efeito sobre o escurecimento das raízes.…”
Section: Introductionunclassified